Optimization of Transportation Mode Selection for EPC Project Logistics Using Analytical Hierarchy Process (AHP): A Case Study of RoRo-Based Inter-Island Material Delivery in Indonesia - Muhammad Shohib; Hanie Teki Tjendani; Jaka Purnama (Universitas Dharma Wacana, 2025)
Efficient logistics management plays a crucial role in the success of EPC projects, particularly when transporting heavy fabricated components across island regions. This study aims to identify the most optimal transportation mode using the AHP based on six key criteria: cost, lead time, risk, load capacity, flexibility, and port accessibility. A hierarchical decision model was developed and assessed by seven expert respondents, with calculations performed using Expert Choice 11. The results indicate that cost, lead time, and port accessibility hold the highest priority weights, reflecting their strategic importance in EPC logistics. The synthesis of criteria and alternative weights identified Roll-on/Roll-off (RoRo) as the most suitable transportation mode, outperforming cargo ships, barges, LCTs, and truck combinations. Validation using actual project data further confirmed this result: the total delivery cost using RoRo amounted to IDR 1,126,000,000, representing a 22% savings compared to the planned budget, and only 1.66% of the total project cost significantly lower than industry benchmarks of 8–11%. The results confirm that AHP constitutes an effective and reliable approach for transportation mode selection in EPC projects. The study offers actionable managerial insights and advances the application of multi-criteria decision-making in construction logistics.